How FinTech affects total factor energy efficiency? Evidence from Chinese cities - Kong, Xinyue; Xu, Tao (Frontiers in Energy Research, 2023)
This study investigates the relationship between financial technology (FinTech) and Total Factor Energy Efficiency (TFEE) using data from a selected sample of 254 city groups in China. We examine how the development of FinTech impacts TFEE from both non-spatial and spatial perspectives. The results from the non-spatial panel model indicate that the development of FinTech has a significant positive impact on TFEE. Comparative studies were conducted using fixed effects (FE), feasible generalized least squares (FGLS) models, and system generalized method of moments (GMM) models, and the main findings remained consistent, confirming the robustness of our conclusions. Spatial autocorrelation results reveal a significant positive spatial spillover effect on TFEE. Both the spatial Durbin model and the dynamic spatial Durbin model demonstrate that FinTech also has a significant positive impact on TFEE, and this effect increases over time. These conclusions remain robust even after considering various spatial weight matrices and alternative TFEE calculation methods. Additionally, we discovered that the digital economy plays a vital role in strengthening the relationship between FinTech and TFEE. Heterogeneity analysis indicates that, in comparison to cities without resource-based economies, the development of financial technology in resource-based cities experiencing growth has a more substantial impact on TFEE. In the context of the integrated development of technology and financial markets, the research findings of this article provide important references for the green production transformation of the government, the State Grid Corporation of China, and other energy companies.